2022
DOI: 10.1097/md.0000000000029474
|View full text |Cite
|
Sign up to set email alerts
|

Lower gastrointestinal bleeding in a male with jejunal Dieulafoy's lesion after successful surgical resection

Abstract: Introduction: Dieulafoy's lesion (DL) presented with small bowel bleeding constitutes a group of rare and potentially life-threatening prognosis. Several case series have described this condition, yet it remains unclear as to what is the optimal treatment and predicted outcome for patients who have been diagnosed. Patient concerns: We present a 21-year-old male experiencing bloody stool for 1 day. Diagnosis: Computed tomography of the abdomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This study aimed to reveal the clinical characteristics of small bowel DLs which are often challenging to diagnose. Our analysis revealed that many patients with DL had underlying diseases and comorbidity index of the patients were relatively high as previously reported 15 (Table 1). Intestinal vessel diseases of the small bowel such as angiodysplasia and ischemic enteritis are often complicated with severe underlying diseases and are related to the peripheral vein [3,19].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study aimed to reveal the clinical characteristics of small bowel DLs which are often challenging to diagnose. Our analysis revealed that many patients with DL had underlying diseases and comorbidity index of the patients were relatively high as previously reported 15 (Table 1). Intestinal vessel diseases of the small bowel such as angiodysplasia and ischemic enteritis are often complicated with severe underlying diseases and are related to the peripheral vein [3,19].…”
Section: Discussionsupporting
confidence: 82%
“…Several hypotheses have been put forward to explain bleeding from DLs. The use of aspirin, warfarin, or nonsteroidal antiin ammatory drugs has been reported in some patients who experience bleeding from DLs [15]; however, no causal link has been established [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been proposed to explain bleeding from DLs. While the use of aspirin, warfarin, or nonsteroidal anti-inflammatory drugs has been observed in some DL bleeding cases [ 15 ], no definitive causal link has been established [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%